Understanding and awareness of dementia in the Sikh community - Uppal, Gobinderjit Kaur (Mental health, religion & culture, 2014)
Previous literature confirms that older black minority ethnic populations are less likely than white populations to contact dementia services in the UK. However, it is unknown whether this is due to a higher or lower prevalence of dementia or due to different needs or coping strategies within these communities. The aim of this study was to explore the understanding and perceptions of dementia amongst Sikhs living in the UK. Six focus groups were involved with 28 Sikh participants who were recruited from Gurdware (Sikh places of worship). Data were analysed using constant comparative methodology. The themes reported in this paper include "awareness and interpretation of the characteristics of dementia", "multiple perspectives of the same symptoms" and "causes of dementia". The findings have been discussed in the context of existing research and provide an introductory insight into informing culturally appropriate interventions.